The association of neonatal jaundice and breast-feeding - Rulina Suradi; Esther H. Situmeang; Taralan Tambunan (Paediatrica Indonesiana, 2001)
To examine the prevalence of jaundice in neonates and its association with breast-feeding, we studied 100healthy breast-fed baby boys during the first 3 - 5 days after birth, delivered in Dr. Cipto Mangunkusumo Hospital. This wasan analytical, cross-sectional study performed prospectively. The study was conducted from April, 1, 1999 to October 15,1999. Jaundice was detected in 94 out of 100 infants (94%). Breast-feeding jaundice was encountered in 26 infants (28%)namely infants whose bilirubin levels was >12 mg/dL by day 3 (CI 95% : 19;37%). Most infants showed bilirubin levels on daytwo, three and five of 6 – 10 mg/dL (62%), 6 – 10 mg/dL (35%) and 12 – 15 mg/dL (34%), respectively. Several factors foundto be contributing to the occurrence of breast-feeding jaundice included : a. breast-feeding frequency (r :- 0.83, p < 0.01), b.mean breast-feeding duration : infants breast-fed for more than 30 minutes have consequences its breast-feeding frequencywas less in compared with those breast-fed in less than 30 minutes. c. time of meconium passage (p< 0.05), meconiumpassage in the first hours after birth played an important part in reducing enterohepatic circulation, d. fecal weight (r =-0.87,p < 0.01), feces retained in the intestine its bilirubin would be deconjugated and reabsorbed subsequently . e. weight loss (p< 0.05). In 11 infants who received blue light therapy there were no abnormalities both in physical and laboratory examinations.